QHBsAg for the Identification of Liver Histological Abnormalities in HBeAg-Negative Chronic Hepatitis B Patients with Normal and Mildly Elevated ALT Levels. (14th July 2022) - Gan, Qinyi; Huang, Yan; Zhu, Chuanwu; Zhao, Shuang; Fu, Haoshuang; Cai, Minghao; Wang, Jiexiao; Zhang, Chenxi; Guo, Simin; Cao, Zhujun; Xie, Qing
Abstract : Backgrounds . Noninvasive detection of histological abnormalities remains challenging in patients with HBeAg-negative chronic HBV infection with normal or mildly elevated levels of alanine aminotransferase (ALT). This study aimed to assess the utility of serum quantitative hepatitis B surface antigen (qHBsAg) in identifying significant histological lesions in this population. Methods . This is a single-center study with retrospective analysis of 392 treatment-naive patients of HBeAg-negative chronic HBV infection with normal or mildly elevated levels of ALT. Results . In this cohort, significant necroinflammation and fibrosis were found in 69.4% and 61.5% of patients, respectively. Patients with qHBsAg >1000 IU/mL ( N = 236) had more hepatic inflammation of ≥ G 2 (75.4% vs. 60.9%, P < 0.01 ) or fibrosis ≥ S 2 (66.1% vs. 54.5%, P < 0.05 ) compared to those without ( N = 156). Serum HBsAg (cutoff point = 1000 IU/mL), aspartate aminotransferase (AST) level (cutoff point = 25 IU/L), age (cutoff point = 40 years), and HBV family history were identified as independent predictors of significant histological abnormalities in multivariate logistic analysis. Conclusions . A significantly higher proportion of patients with histological abnormalities were found in patients with qHBsAg >1000 IU/mL than those without. The qHBsAg level together with age, AST, and family history of HBV infection could be used as an algorithm to help noninvasive patient selection for antiviral therapy.